Peningkatan Hasil Belajar Kognitif Melalui Aplikasi Smart App Creator - Udin Kasmudi (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2023)
This researcher aims to describe and analyze the application of student learning outcomes using the smart app creator application. The research method used is a descriptive method that describes the implementation of learning by using a smart app creator. The subjects in this study were 32 students of class VIIB Madrasah Tsanawiyah Negeri 1 Grobogan. The instrument used is the distribution of questionnaires and evaluation tests in the form of description questions . The results obtained from material experts 90.50% and media experts 90.30% from the two experts obtained valid categories. The implementation of learning with the smart app creator application on adolescent body development materials can improve student learning outcomes. student learning outcomes before implementing application learning using the smart app creator application obtained data that as many as 46.8% of students had scored above the KKM, while the rest had not met the KKM, increased by 46% to 93.7% with a good category in learning using applications smart app creator on teenage body development material Abstrak belajar peserta didik menggunakan aplikasi smart app creator. Metode penelitian yang digunakan adalah metode deskriptif yang menggambarkan pelaksanaan pembelajaran dengan menggunakan smart app creator. Adapun subyek dalam penelitian ini yaitu 32 siswa kelas VIIB Madrasah Tsanawiyah Negeri 1 Grobogan. Instrumen yang digunakan yaitu penyebaran angket dan tes evaluasi berupa soal uraian. Hasil yang diperoleh dari ahli materi 90.50% dan ahli media 90.30% dari kedua ahli tersebut diperoleh kategori valid. Implemantasi pembelajaran dengan aplikasi smart app creator pada materi perkembangan tubuh remaja dapat meningkatkan hasil belajar siswa. hasil belajar siswa sebelum melaksanakan pembelajaran penerapan menggunakan aplikasi smart app creator diperoleh data yaitu sebanyak 46,8% peserta didik telah mendapatkan nilai diatas KKM, sedangkan sisanya belum memenuhi KKM, bertambah sebesar 46% menjadi 93,7% dengan kategori baik dalam pembelajaran menggunakan aplikasi smart app creator pada materi perkembangan tubuh remaja